Banco del Sur: it ?s logic and needs - Romero Cevallos, Marco (2007)
The author locates the process of the creation of the Banco del Sur and it ?s ups and down within the global trend of regional monetary and financial cooperation after the Asian crisis in 1997, as well as within the historic tendencies of Latin America.